A Mathematical Model for the Description of Pulsed Thermography Applied to the Detection of Hidden Text - Giovanni Caruso; Noemi Orazi; Stefano Paoloni; Ugo Zammit; Fulvio Mercuri (Engineering Proceedings, 2023)
Non-destructive techniques for the analysis of cultural heritage items are of the outmost importance in order to understand better the artworks, to assess their conservation conditions and to evaluate a possible restoration intervention. Among these techniques, pulsed infrared thermography plays an important role, since it is simple and quite powerful. A standard experimental setup employs flash lamps for the delivery of a pulse of visible light to heat the sample and an infrared camera to record the consequent radiation emission. In this study, this technique was applied for studying ancient manuscripts and, in particular, for revealing hidden text buried under the end leaves of the book. A mathematical model developed by the authors is briefly detailed. The finite element method was employed to numerically solve the model equations and perform numerical simulations. The numerical results highlight the influence of some parameters involved in this phenomenon and can be used for a quantitative analysis of the experimental findings.